Eulalie, un système documentaire pour préserver la musique électroacoustique basé sur l’ontologie Dorémus - Bernard Jacquemin; Clarisse Bardiot; Alexandre Michaan; Jeanne Westeel; Oudom Southammavong; Daniel Koskowitz (Humanités Numériques)
Eulalie is an operational, open-source, and free information system dedicated to electroacoustic music for the documentation and preservation of works. It is based on the Dorémus ontology, which we adapt to the specific field of electroacoustic music, and on its implementation in a database (Heurist, used together with Nakala to host the documents). The project was born in the context of Art Zoyd Studios, a center for musical creation. One of the missions of this center is to preserve the repertoire of the 20th- and 21st-century pieces involving electronics. The principles of interoperability and open data have guided the different choices made throughout the project. Thus, not only is it possible to make the content of the Art Zoyd Studios information database interact with other resources on music, but the Eulalie system itself can be used by other institutions facing similar problems.